2016
DOI: 10.1007/s12540-016-5504-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical quenching rate for high hardness and good exfoliation corrosion resistance of Al-Zn-Mg-Cu alloy plate

Abstract: By means of the end-quenching technique, we investigated the relationship between quenching rate and hardness as well as exfoliation corrosion rating for Al-2.21 Zn-3.59 Mg-0.45 Cu-0.038 Zr (at%) alloy plate. In order to achieve an exfoliation corrosion rating of P or EA, the quenching rate must be greater than approximately 460°C/min and 300°C/min, respectively, and the drop degree in hardness should simultaneously be lower than approximately 2.0% and 3.5%, respectively. The results of microstructural and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 26 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Song et al [15] observed an increase in the exfoliation corrosion sensitivity of the AA7050 alloy with a decreasing quenching rate. Li Dongfeng et al [16] discovered that as the quenching rate decreased from 2160 • C/min to 100 • C/min, the exfoliation corrosion grade of Al-5Zn-3Mg-1Cu alloy sheets gradually shifted from P grade to ED grade. Liu et al [17] revealed that the maximum exfoliation corrosion depth of AA7055 alloy gradually increases as the quenching rate decreases, indicating an ascending trend in exfoliation corrosion sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [15] observed an increase in the exfoliation corrosion sensitivity of the AA7050 alloy with a decreasing quenching rate. Li Dongfeng et al [16] discovered that as the quenching rate decreased from 2160 • C/min to 100 • C/min, the exfoliation corrosion grade of Al-5Zn-3Mg-1Cu alloy sheets gradually shifted from P grade to ED grade. Liu et al [17] revealed that the maximum exfoliation corrosion depth of AA7055 alloy gradually increases as the quenching rate decreases, indicating an ascending trend in exfoliation corrosion sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This etchant was also used to reveal the grain structure of high strength 7000 series ingot metallurgy alloys. For instance, it could give good results of recrystallized grains and even subgrains in some 7000 series aluminum alloys [2][3][4], and it was likely because grain boundaries (GBs) and subgrain boundaries (SGBs) in these alloys could be preferentially attacked during immersion in this etchant. In high strength 7000 series aluminum alloys, the microstructure is often very complex due to partical recrystallization and intermetallic particles (e.g.…”
Section: Introductionmentioning
confidence: 99%